Komunikasi dalam Pandangan al-Quran - Sulkifli; Muhtar (PAPPASANG, 2021)
The objective of this research is to find out the concept of communication in holy Qoran. This research is qualitative research which applied social-theology approach. The result of this research reveals that the Qoran illustrates the concept of communication to be several forms. Therefore, muslim scholars claim that there are eight communication forms which mentioned in holy Qoran, those are qaul karim, qaul ma’ruf, qaul layyin, qaul adzim, qaul balig, qaul maisur, qaul tsaqil, and qaul sadid. Farther, the Qoran informs that in communication, one needs to consider the communicant to achieve an intentional main. The determining of communication form chose to be used has offerd in Quran as an alternative way in public communication area.